Hegemoni Kiai di Desa Payaman Solokuro Lamongan pada Pemilu 2019 - Sa'adah, Khoridatus; Fauzi, Agus Machfud (State Islamic Institute of Kudus (IAIN Kudus), 2021)
A Kiai has a high position both socially and spiritually that affects the power of influence over society's choices. The writing was intended to analyze the travel process of hegemoni by Kiai as a sales figure for the golongan karya political party. The research approach used is descriptive qualitative through interviews and observations at the Darul Ma 'arif village Payaman Solokuro Lamongan. The hegemonic theory of Antonio gramsci was used as a basis for analysis. The final result is that the hegemoni sequence of Kiai is absorbed in two parts. This division is based on the difference in age and background. The first group is a society that is over 60 years old and hegemoni is taking a spiritual approach. Its real form, the practice of hegemony was melted down during recruitment. Intellectual ramming is directed as a measure of obedience to the strings to receive a blessing. The second group is scolars and educators. Hegemoni in this group uses discussion forums or coordination meetings by all members of the foundation. The hegemonic column for the educated and more rational group of educators. The real inversion, ramming was done by showing a good track record by the golongan karya party.